Dissecting the role of single nucleotide polymorphism of lymphotoxin beta gene during pig domestication using bioinformatic and experimental approaches - R. B. Aitnazarov; E. V. Ignatieva; N. E. Bazarova; V. G. Levitsky; S. P. Knyazev; Y. Gon; N. S. Yudin (Вавиловский журнал генетики и селекции)
Studies of wild and laboratory animals have revealed a trade-off between reproductive success and immunity. Therefore, it is likely that domestication favored selection of individuals with high reproductive performance but low immunity. The low responsiveness of the immune system could become hereditary through fixation of genes with “unfavorable” mutations in populations. The objectives of this work are: 1) determination of frequencies of genotypes and alleles of the rs340283541 SNP in the gene for the lymphotoxin beta (LTB) cytokine in pigs of domestic breeds and wild boars; 2) investigation of the expression of LTB mRNA in minipigs with different genotypes, and 3) bioinformational analysis of the putative functional role of the SNP. The frequency of the GG genotype in the wild boar sample was significantly lower than in the pooled sample of domestic pigs. The LTB mRNA expression rate in the lymph node of minipigs with genotype GG tended to increase (p < 0.06) in comparison with carriers o allele A. The rs340283541 SNP occurs in a DNA motif highly conservative among 11 mammalian species; thus, it may be of functional significance. Context analysis shows that allele A has putative binding sites for  transcription factors BRN-2 and AP-1, whereas allele G has binding sites for transcription factors RFX1, ISGF3 (site ISRE), and USF expressed in cells of the immune system. Thus, pig domestication was accompanied by an increase in the frequency of the GG genotype for the rs340283541 SNP, occurring in the 3’ region of the LTB gene. It is likely that the GG genotype is associated with elevated LTB mRNA expression in the lymph node tissue. This increase may be related to the formation of binding sites for RFX1, ISRE, and USF and/or disruption of binding sites for BRN-2 and AP-1. A linkage disequilibrium between rs340283541 and another functionally significant mutation in LTB is also conceivable.